INFLUENCE BOARD OF DIRECTOR CHARACTERISTICS AND LIQUIDITY ON FINANCIAL PERFORMANCE - Dewi Komariah; Eny Purwaningsih (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study was conducted with the aim of analyzing the influence of board of directors characteristics and liquidity levels on the financial performance of consumer sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. The independent variables in this study consist of board size (Board Size) measured by the total number of board members; board independence (Board Independence) calculated by comparing the number of independent board members to the total board members; board diversity (Board Diversity) calculated by calculating the proportion of female board members to the total board members; board composition (Board Composition) measured by the proportion of board members with master's degrees; and liquidity (Current Ratio) obtained by comparing current assets to current liabilities. Meanwhile, the dependent variable in this study is financial performance measured using Return on Assets (ROA), which is the ratio between net profit and total assets. The sample in this study consists of 15 consumer sector companies selected over five years of observation, resulting in 75 observational data. This study applies multiple linear regression analysis methods with the support of SPSS software, and is equipped with classical assumption tests to ensure the validity of the model used. Simultaneous test results show that all independent variables collectively have a significant influence on financial performance. Partially, board size, board composition, and liquidity were found to have a positive and significant effect on financial performance, while board independence and board diversity did not. This study contributes to strengthening empirical evidence that certain board characteristics and liquidity conditions can be strategic considerations in efforts to improve corporate financial performance, particularly in the consumer sector.